2021
DOI: 10.3390/app11104323
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Numerical Analysis of Subsurface Delamination Detection in Concrete Slabs via Infrared Thermography

Abstract: One of the concerns about the use of passive Infrared Thermography (IRT) for structural health monitoring (SHM) is the determination of a favorable period to conduct the inspections. This paper investigates the use of numerical simulations to find appropriate periods for IRT-based detection of subsurface damages in concrete bridge slabs under passive heating along a 1 year of time span. A model was built using the Finite Element Method (FEM) and calibrated using the results of a set of thermographic field insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Hiasa et al [159] concluded that seasonal effects were minor on the horizontal plane in Florida. In contrast, Pozzer [173] mentioned that spring and summer were desirable for IRT in Brazil because of high daily ambient temperature change. Therefore, preferred seasons for IRT depend on the region.…”
Section: Othersmentioning
confidence: 97%
“…Hiasa et al [159] concluded that seasonal effects were minor on the horizontal plane in Florida. In contrast, Pozzer [173] mentioned that spring and summer were desirable for IRT in Brazil because of high daily ambient temperature change. Therefore, preferred seasons for IRT depend on the region.…”
Section: Othersmentioning
confidence: 97%
“…Civil infrastructure, such as bridges and concrete pavement, requires maintenance to ensure safety and serviceability [1]. Even though concrete is inherently a durable material, civil infrastructures are susceptible to time-dependent deteriorations due to their exposure to various degradation mechanisms such as abrasion, moisture cycles, corrosion of reinforcements, and so on [2,3]. Particularly, subsurface deteriorations are invisible through visual inspection until the defects convert into a severe condition [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recent advancements in infrared sensors, image processing, and UAVs, UAVbased IRT has demonstrated promising results in concrete delamination detection in recent studies [19,[24][25][26][27][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]43,47,49,50]. These studies reported comparable or better results compared to other non-destructive evaluation (NDE) methods [23,42,51].…”
Section: Introduction 1concrete Deck Delamination Detection Using Inf...mentioning
confidence: 99%